Subduing the nail barrier with novel herbal penetration enhancers for transungual delivery system - Singh, Vikram; Gupta, R. D.; Teotia, U. V. S. (Journal of Applied Pharmaceutical Research, 2015)
Nail fungal infections are very common and also very difficult to treat because of nail morphology, deep penetrability of infectious agent inside nail plate and poor permeability of the nail plate. Transungual delivery shall be the first choice for treatment of nail infection if we get the effective penetration enhancers without causing the serious problem. In this study we tried to scanning some extracts penetration potency through the human cadaver nail plate.ÃÂ